Some basic properties and fundamental relations for discrete Muckenhoupt and Gehring classes - S. H. Saker (Advances in Difference Equations, 2021)
Abstract In this paper, we prove some basic properties of the discrete Muckenhoupt class A p $\mathcal{A}^{p}$ and the discrete Gehring class G q $\mathcal{G}^{q}$ . These properties involve the self-improving properties and the fundamental transitions and inclusions relations between the two classes.